Darowizny na rzecz małżonków w świetle regulacji prawnej obowiązującej w Królestwie Polskim - Dorota Wiśniewska-Jóźwiak (Czasopismo Prawno-Historyczne)
Donations in the Kingdom of Poland were regulated by the Napoleonic Code. However, apart from a couple of general rules, the Napoleonic Code did not provide for any special regulation that would be exclusively applicable to the specific kind of donations such as donations made by one spouse to the other. Acts-in-law pertaining to donations could be executed either in the same deed (notarial act) together with the pre-nuptial agreement, or as a separate deed.